2007
DOI: 10.1093/her/cym063
|View full text |Cite
|
Sign up to set email alerts
|

Social contexts in adolescent smoking: does school policy matter?

Abstract: According to an ecological perspective in psychology and in line with social cognitive theory, smoking behaviour is determined by different social contexts (for example, peers, family and school) providing adolescents with important role models. This paper investigates the effects of personal characteristics as well as family, peer and school context variables on youth smoking behaviour. We hypothesize that school smoking policy variables predict adolescents' smoking in addition to other context variables. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 26 publications
5
61
2
3
Order By: Relevance
“…Our results highlight the great importance of parental attitudes to smoking by adolescents. In agreement with previous results (Piontek et al, 2008;Jackson, Henriksen, Dickinson, y Levine, 1997), we found that smoking was highest in those with the poorest academic performance, independent of other variables.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results highlight the great importance of parental attitudes to smoking by adolescents. In agreement with previous results (Piontek et al, 2008;Jackson, Henriksen, Dickinson, y Levine, 1997), we found that smoking was highest in those with the poorest academic performance, independent of other variables.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of adolescent smoking has been found to vary among school centers (Aveyard, Markham, y Cheng, 2004) and attending a school that tolerates smoking has been associated with a significantly higher percentage of students that start consuming tobacco (O'Loughlin et al, 2009;Barnett et al, 2007;Moore, Roberts, y Tudor-Smith, 2001;Piontek et al, 2008;Wakefield et al, 2000). Moreover, a longitudinal study performed at secondary schools in England (Aveyard et al, 2005) showed that the school center alone, irrespective of the characteristics of the students, influenced the percentage of smoking students.…”
mentioning
confidence: 99%
“…Specifically, the model included factors associated with adolescent tobacco use, based on individual-level (Level-1) variables and school-level (Level-2) variables that convey information typically used to characterize school environments 1,11,[14][15][16]35,[40][41][42] .…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Research increasingly demonstrates that tobacco use is influenced by a myriad of socio-environmental factors. For instance, studies show notable variation of smoking prevalence rates across schools, regardless of individual-level factors [11][12][13] , suggesting direct pathways between schools and adolescent tobacco use, tobacco attitudes, and motivation to quit tobacco [14][15][16] . School-level determinants are known to explain between 4% to 40% of the variation in smoking, across both middle and high-school aged students 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A study in Denmark found that almost 90% of students have seen a teacher smoking within school premises although a school no-smoking policy exists 13 , butis poorly enforced. Tobacco use among teachers in school influences smoking behaviour of school students and having a strict tobacco-free policy in school reduces smoking among school students 9,14 . Teachers play an important role in implementing this policy and yet there is a paucity ofresearch on the teacher's perceptionof this policy.…”
mentioning
confidence: 99%